Классификация лунных магматических пород - Богатиков О. А. Олег Алексеевич; Гоньшакова В. И. Валентина Ивановна; Фрих-Хар Д. И. Дмитрий Иосифович; Кочемасов Г. Г. (Москва, Недра, 1985)
Авт. указаны на обороте тит. л.